Pengaruh Kepuasan Pengguna, Kualitas Platform E-Learning, dan Ketersediaan Sumber Daya terhadap Prestasi Belajar Mata Pelajaran Ekonomi SMA Negeri 1 Karanganom - Nindita Fadhila; Nenden Susilowati (Pusat Riset dan Inovasi Nasional, 2025)
The Effect Of User Satisfaction, E-Learning Platform Quality, And Resource Availability On Learning Achievement Of Economics Subjects At State High School 1 Karanganom. This study aims to determine the effects of user satisfaction, e-learning platform quality, and resource availability on student achievement in Economics at SMA Negeri 1 Karanganom. The research used a quantitative approach with a survey method and purposive sampling technique. Data were collected through questionnaires and achievement tests, validated by Economics Education lecturers and high school teachers. Multiple regression analysis was employed. The results indicate that both user satisfaction and e-learning platform quality have a significant effect on student achievement. Meanwhile, resource availability does not show a positive influence, but it still has a significant effect on learning outcomes. These findings highlight the importance of enhancing user experience and digital platform quality to support effective learning strategies.